2014
DOI: 10.1007/s00198-014-2978-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal collagen cross-links and matrix hydration in high- and low-turnover chronic kidney disease

Abstract: Purpose/Introduction Clinical data have documented a clear increase in fracture risk associated with chronic kidney disease (CKD). Preclinical studies have shown reductions in bone mechanical properties although the tissue-level mechanisms for these differences remain unclear. The goal of this study was to assess collagen cross-links and matrix hydration, two variables known to affect mechanical properties, in animals with either high or low turnover CKD. Methods At 35 weeks of age (>75% reduction in kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…Iwasaki et al observed changes in whole bone storage modulus and tan delta in rats after 16 weeks with 5/6 Nx and a high-phosphate diet [Iwasaki et al, 2015]. Meanwhile, in a Cy/+ genetic CKD model in rats, diseased bones had significantly lower ultimate stress, a trend towards lowered toughness, and no change in modulus as measured from three-point bending [Allen et al, 2014]. In another study with Cy /+ rats, CKD significantly reduced ultimate stress and stiffness, while energy to failure was not changed [Moe et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwasaki et al observed changes in whole bone storage modulus and tan delta in rats after 16 weeks with 5/6 Nx and a high-phosphate diet [Iwasaki et al, 2015]. Meanwhile, in a Cy/+ genetic CKD model in rats, diseased bones had significantly lower ultimate stress, a trend towards lowered toughness, and no change in modulus as measured from three-point bending [Allen et al, 2014]. In another study with Cy /+ rats, CKD significantly reduced ultimate stress and stiffness, while energy to failure was not changed [Moe et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The current work addressed an important inconsistency in whether microscale material properties change with CKD; namely, through placing arrays in a location of actively forming bone, lower bone material quality was readily observed. A preponderance of evidence collected from this study and others now suggests that CKD does affect bone material properties, and that these properties may involve the quantity of mineral or its maturation ( e.g., current work, Iwasaki et al, 2011, Iwasaki et al, 2015), or the collagen network supporting mineralization [Allen et al, 2014]. Looking ahead, a site-matched approach employing nanoindentation alongside Raman Spectroscopy may reveal greater detail about how formation and maturation of bone mineral and matrix are specifically altered with CKD, and how these changes contribute to diminished microscale mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…This is quite surprising given the known preferential effect of CKD on cortical bone [37]. The effects of BP on tissue mineralization, or other aspects of the matrix for that matter (mineral crystallinity, heterogeneity, collagen structure/ cross-linking, hydration, microdamage), are nonexistent in part because the effects of CKD alone have only recently been explored [38,39]. Given that BPs are known to affect tissue properties in ways that have both positive and negative influence on bone integrity [40], these ultra structural assessments are desperately needed to understand the full picture of BP effects.…”
Section: Volume Density and Mineralizationmentioning
confidence: 91%
“…The hydration shell of collagen is provided by small proteoglycans SLRPs (Small Leucine-Rich Proteoglycans) that decorate the surface of collagen fibrils 61 . The precisely located, enzymatic covalent crosslinks in the collagenous scaffold confine bound water to the interfibrillar space 62 . As a result of the crosslinking, the collagenous matrix is effectively a continuous framework with limited extensibility that cannot swell to accommodate bound water, and the osmotic pressure provided by proteoglycans builds up to the kPa range [63][64][65] .…”
Section: Biomechanical Implications Of Inhibition and Promotion Of MImentioning
confidence: 99%